MANAJEMEN KEPALA SEKOLAH DALAM IMPLEMENTASI KURIKULUM MERDEKA (Studi Kasus Sekolah Penggerak SD Negeri 01 Percontohan Meulaboh) - Syarifuddin, Syarifuddin; Yanti, Hera (LPPM-UNIKI, 2024)
The research focuses on the application of principal management in the implementation of the independent curriculum, studies at the bullying school of SD Negeri 01 Meulaboh, West Aceh. This research uses a descriptive qualitative approach. The role of the school principal is to ensure that the implementation of the independent curriculum is in accordance with the indicators that have been prepared. Organizational techniques by functioning all lines, according to their respective tasks and portions. The principal ensures that his teachers implement the implementation of the independent curriculum, by completing teacher administration, implementing the independent curriculum in class, and implementing the P5 independent curriculum project. As well as carrying out the process of monitoring and evaluating the independent curriculum in stages, including; setting standards, implementing activities, analyzing deviations, and taking corrective action.